STABILITY OF SOLUTIONS OF SYSTEMS WITH IMPULSIVE ACTIONS - Гургула, Степан Іванович; Собкович, Роман Іванович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
Criteria’s of stability, asymptotic stability and non-stability of simple solution in an analogy to those according to the secondary Liapunov’s method for differential equations without impulses, were issued for system of ordinary differential equations with impulsive action in the fixed moments of time.